Pre-operative transnasal endoscopy as a predictor of difficult airway: A prospective cohort study. Issue 2 (February 2020) - Gemma, Marco; Buratti, Luca; Di Santo, Davide; Calvi, Maria R.; Ravizza, Alfredo; Bondi, Stefano; Bussi, Mario; Beretta, Luigi
Abstract : BACKGROUND: Consequences of failed endotracheal intubation can be catastrophic and predicting difficulty is therefore a critical issue. There is no consensus on the best way to predict difficulty. OBJECTIVE: To evaluate the role of transnasal flexible endoscopic laryngoscopy (TFEL), a minimally invasive procedure, in the prediction of difficult intubation. DESIGN: Prospective cohort study. SETTING: San Raffaele Hospital, Milan, a tertiary university hospital. PATIENTS: One hundred and sixty nine adults scheduled for elective ear, nose and throat surgery under general anaesthesia with pre-operative TFEL. INTERVENTION: In addition to routine pre-operative evaluation by an anaesthesiologist, glottis exposure during TFEL was assessed with a scoring system similar to the modified Cormack–Lehane (MCL). MAIN OUTCOME MEASURES: The extent to which TFEL improves the prediction of difficult direct laryngoscopy, measured with the MCL score, and of difficult intubation, measured with the intubation difficulty scale score. RESULTS: When added to bedside evaluation, TFEL performed during tongue protrusion significantly ( P  = 0.005) improved the prediction of MCL. The area under the receiver operating characteristics curve was 0.75 [95% confidence interval (CI) 0.67 to 0.83] vs. 0.65 (95% CI 0.58 to 0.74). For the intubation difficulty scale ( P  = 0.049), the area under the receiver operating characteristics curve was 0.70 (95% CI 0.61 to 0.80) vs. 0.66 (95% CI 0.58 to 0.74). CONCLUSION: TFEL is a useful tool in predicting difficult intubation, improving predictability of routine bedside evaluation. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02671877.